1997
DOI: 10.1111/j.1365-3156.1997.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐DNA tagging reveals a novel cDNA triggering cytokinin‐ and auxin‐independent protoplast division

Abstract: basis of action in plants is fragmentary. Plants may synthes-Cordeiro 1 , Els Prinsen 2 , Jeff Schell 1 and Richard ize cytokinins either directly by addition of isopentenylpyro-Walden 1,* phosphate to AMP by an adenylate:isopentenyltransferase 1 Max-Planck-Institut fü r Zü chtungsforschung, Carl-von-(cytokinin synthase) producing isopentenyladenosine 5Ј Linne-Weg 10, 50829 Kö ln, Germany, and phosphate ([9R-5ЈP]iP) which in turn serves as an inter-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…These findings are in contrast to data presented in previous publications ( Ichikawa et al . 1997 ; Miklashevichs et al . 1997 ; van de Sande et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are in contrast to data presented in previous publications ( Ichikawa et al . 1997 ; Miklashevichs et al . 1997 ; van de Sande et al .…”
Section: Resultsmentioning
confidence: 99%
“…Using activation T‐DNA tagging, cytokinin‐independent mutants of Arabidopsis have indeed been generated which allow the identification of a gene involved in cytokinin signal transduction ( Kakimoto 1996), thus confirming the general validity of the activation gene tagging approach. However, it was reported that cultured cells isolated from the tagged mutant plants cyi1 ( Miklashevichs et al . 1997 ), axi4/1 ( Harling et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant mutation obtained allows selection for a predetermined phenotype. To date, this approach has been used to create tobacco protoplast lines able to grow in the absence of auxin (39); cytokinin (77), or in the presence of an inhibitor of polyamine biosynthesis (28); as well as a mutant callus of Catherostigma plantagineum changed in response to dessication (29); and Arabidopsis callus able to form shoots in the absence of cytokinins (50). The genes tagged include axi1, which affects gene expression (115); cyi1, a small peptide growth factor (77) and cki1, a two-component receptor kinase (50); and factors involved in the regulation of seed maturation (88).…”
Section: Activation Taggingmentioning
confidence: 99%